Comparison Study Of Packet Classification Algorithms In Wired Networks - Marwan Salim Mahmoud; Awos Khazal Ali (College of Education for Pure Sciences, 2012)
ABSTRACT The packet classification technique play an important role for many internet advanced services that require the capability to distinguish traffic in different flows, such as routers and security services like firewalls and packet filters. This paper provide a brief introduction for packet classification process. Beside, the categorization of the algorithms that classify packets to different flow. Also, this paper give a brief description of two homogenous algorithms (algorithms that belongs to same category), these algorithms are Tuple Space Search (TSS) and Recursive Flow Classification (RFC). Furthermore, this paper provides a comparative evaluation of these two algorithms (TSS & RFC). The evaluation of these techniques are done under Linux REDHAT 5.0 platform in order to analyze and compare their performance between each other. In particular, the comparison focuses on achieving a good classification time in classification process and, low memory consumption rate.